Role and health benefits of different functional food components. - Guiné, Raquel (2013)
Functional food components are potentially beneficial components found naturally in foods or added to them as functional ingredients, and include carotenoids, dietary fiber, fatty acids, flavonoids, isothiocyanates, phenolic acids, plant stanols and sterols, polyols, prebiotics and probiotics, phytoestrogens, soy protein , vitamins and minerals. At present, professionals are recognizing that some functional components of foods have a major role in health enhancement. In fact, the big importance of these “bioactives” present in many foods, either naturally or added, has lead many scientists of different fields to conduct studies aimed for establishing the scientific basis that supports and validates the benefits of a particular food or component for the human health. It appears that people should strive to consume a wide variety of foods such as to assure the ingestion of compounds such as carotenoids, fiber, flavonoids, specific fatty acids, minerals, prebiotics and probiotics, phytoestrogens, soy protein and vitamins, among others, in order to reduce the risk of developing some diseases, or even to help curing others. In the present work, an examination of the characteristics of these compounds, the study and repercussions of these “bioactives molecules” allied to their ability to prevent and/or cure certain diseases will be object of study, based on recent evidence published in the medical journals.